Performance of agri-horti-silvi system in the hot arid region of Rajasthan - Singh, Bilas (Indian Journal of Agroforestry, 2020)
The performance influence of a combination of horticulture species (Zizyphus mauritiana, Cordia mixa and Emblica officinalis) and silviculture (Prosopis cineraria, Ailanthus excelsa and Colophospermum mopane) species on wheat (Triticum aestivum L.) yield was studied for five year under supplementary irrigation with a view to enhance land productivity in term of fruit, fodder and food in arid environment of Rajasthan. Horti and silvi species were planted in alternate tree with 9 possible combinations and wheat was intercropped for five years. Survival and collar diameter of trees were greater (P<O.05) in integrated agroforestry, as compared to the control plots. Height of A. excelsa, C. mopane, C. mixa and P.Â cineraria trees was 132%, 61%, 57% and 47% greater in cropped (agroforestry) plots as compared to the sole tree plot after five years age. Effect of planted species on crop yield was not significant in initial 4 years, but in fifth year, grain yield of crop was significantly low (23%) in C. mixa and C. mopane combination plot as compared to the sole agriculture plot. However, the production of the tree leaf as fodder was complementary to the overall production.